Frequency of Vitamin D Deficiency in Maintenance Hemodialysis Patients - Zahid ul Zahideen, Ubaid Ullah, Raja Muhammad Rashid, Syed Azra, Hafiz Furqan Ahmad Khan, Zahid Nabi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of vitamin D deficiency in maintenance hemodialysis patients. Design of the Study: It’s a descriptive cross-sectional study. Study Settings: This study was carried out at Department of Nephrology, KRL Hospital, Islamabad from 14th November 2017 to 13th May 2018. Material and Methods: There were 85 ESRD (GFR 15 ml/min) patients between the ages of 25 and 65, male and female. Acid reflux, vitamin D supplementation, and steroid use in the last month all ruled out. Vitamin D levels were measured in each patient’s 3 ml blood sample, which was delivered to the institution’s pathology laboratory for analysis. Results of the Study: From 25 to 65 years old, participants in this study had a mean age of 51.85 12.83 years. Seventy-nine percent of the patients (79%) ranged in age from 46 to 65. A male to female ratio of 1.4:1 was observed among the 85 total patients, with 49 (57.65 percent) and 36 (42.35%) patients being men. In our study, the average length of illness was 10.61±7.90 years. Dialysis lasted an average of 5.14±8.14 months. The average BMI was 23.54±4.88 kg/m2 (standard deviation). In our study, we observed that 70.59 percent of patients on maintenance hemodialysis were deficient in vitamin D. Conclusion: It is concluded that prevalence of vitamin D deficiency in individuals on continuous hemodialysis is extremely high.